THE ROLE OF ENVIRONMENTAL KNOWLEDGE AND ATTITUDE IN SHAPING THE BEHAVIOR OF SME ACTORS (A MULTI-CASE STUDY IN KEDIRI CITY) - Yuliani, Yuliani; Sugiarto, Suprihantosa (An-Nisbah: Jurnal Ekonomi Syariah, 2024)
Abstract: In Indonesia, Small and Medium Enterprises (SMEs) make up approximately 99% of the total businesses and absorb 97% of the workforce, making SMEs a key contributor to the economic sector. However, the waste produced by SMEs is also considerable when compared to large-scale businesses. Research discussing the environmental impact of SME economic activities is still very limited, despite the importance of the relationship between SMEs and the environment as a critical issue to study. The aim of this study is to obtain an in-depth and holistic description of the knowledge, attitude, and production behavior of SME actors regarding environmentally conscious production. This research is qualitative in nature. Three data collection procedures will be used in this study: interviews, observations, and documentation. Based on the analysis conducted, the research findings are: (1) business owners have limited knowledge of environmentally conscious economics; (2) SME owners have a positive attitude towards environmentally conscious business practices; (3) some SMEs still use raw materials harmful to the environment and do not engage in waste management. Keywords: Knowledge, Attitude, Environmentally Conscious Behavior Abstrak: Di Indonesia, jumlah pelaku Usaha Kecil dan Menengah (UKM) sekitar 99% dari total perusahaan/usaha yang ada di Indonesia dan menyerap 97% tenaga kerja sehingga UKM memainkan peran penting memberikan konstribusi di sektor ekonomi. Namun, limbah yang dihasilkan oleh UKM juga tidak kalah besar jika dibandingkan dengan usaha skala besar. Penelitian yang membahas dampak aktivitas ekonomi dari UKM terhadap permasalahan lingkungan juga masih minim sekali. Padahal, antara UKM dan lingkungan merupakan permasalahan yang penting untuk diteliti. Tujuan dari penelitian ini adalah untuk memperoleh deskripsi secara mendalam dan holistik tentang pengetahuan, sikap, perilaku produksi yang dimiliki oleh pelaku UKM tentang produksi berwawasan lingkungan. Sehingga penelitian ini merupakan penelitian kualitatif. Ada tiga prosedur pengumpulan data yang akan digunakan dalam penelitian ini, yaitu: wawancara, observasi, dan dokumentasi. Berdasarkan analisis yang telah dilakukan, temuan penelitian adalah (1) pengusaha memiliki pengetahuan yang terbatas tentang ekonomi berwawasan lingkungan. (2) pemilik UKM memiliki sikap yang setuju/mendukung terhadap usaha yang berwawasan lingkungan. (3) masih terdapat UKM yang mengunakan bahan baku yang membahayakan lingkungan dan tidak melakukan pengolahan limbah. Kata Kunci: Pengetahuan, Sikap, Perilaku Berwawasan Lingkungan